Faktor-Faktor Yang Memengaruhi Volume Impor Beras Di Indonesia - Andry Suryo Wibowo; Sri Marwanti (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2023)
Rice is one of the agricultural products that experience many problems in providing national food stocks. Constraints on rice stocks in Indonesia have resulted in price increases, especially for low-income people. Insufficient rice production encourages rice imports by the government to meet national needs. The research aims to determine the factors that influence rice imports in Indonesia. The basic research method is a quantitative descriptive method. Secondary data was used in 1993-2022. Data analysis uses multiple linear regression. The results of the analysis show: (1) Together, the variables of rice harvest area, population, rupiah exchange rate, rice consumption, and rice stock have a significant effect on rice imports. (2) The variables of rice harvest area, rupiah exchange rate, and rice stock do not individually have a significant effect on rice imports. On the other hand, the variables of population and rice consumption have a significant effect individually. (3) The variables of population and rice consumption have a positive and significant influence on rice imports. The government is advised to focus on rice import policies by considering fluctuations in domestic consumption and population which have a significant impact, while also monitoring the stability of the rupiah exchange rate to anticipate potential impacts in the future.